The Relevance of Social Studies Education in the Independent Curriculum to the Thoughts of Ki Hadjar Dewantara - Yunike Sulistyosari,; Habibi Sultan,; Hermon Mauritis Karwur,; Manuel E Korompis, (Technium Social Sciences Journal, 2023)
The problem of dehumanization in education is still felt by students in the global era with rapid technological developments. Thus causing a generation of moral value crises. This study aims to find out how the relevance of social studies education to the independent learning curriculum with the thoughts of Ki Hadjar Dewantara. The research method uses the library method with books and articles from journals as sources. Data collection techniques using literature, coding, and recording. This research has findings that IPS Education as a social science discipline has a high social responsibility in upholding democratic values, to create equality and justice in the educational environment. So that all students can enjoy freedom during the learning process. In line with the concept of an independent curriculum which provides opportunities for students to choose and determine methods in the learning process. Relevant to Ki Hadjar Dewantara's thought that education must humanize humans, so students are not oppressed by being dominated by teachers in the learning process. According to Ki Hadjar Dewantara, the concept of independence does not mean freedom to do as you please, but freedom based on order and respect for the rights of others. Independence here does not only apply to students but also applies to educators so that the education and learning process takes place humanely. Social studies education with democratic values and the concept of independence from Ki Hadjar Dewantara has indeed been fully realized in the currently ongoing independent learning curriculum, to achieve education in Indonesia that promotes humanism and justice.